Optimalisasi Pemanfaatan Pekarangan Dengan Budidaya Sistem Aquaponik Di Desa Bandar Sari Kecamatan Padang Ratu, Kabupaten Lampung Tengah, Provinsi Lampung - Gregorius Nugroho Susanto, Tugiyono, Nuning Nurcahyani dan Jani Master (FMIPA Universitas Lampung, 2022)
Vegetables and fish are important sources of food and nutrition for humans. The need for vegetables and fish is the main thing that needs to be fulfilled so that it becomes one of the important things for the community. This need can actually be met from the results of business or self-cultivation in the yard of the house, especially for people who still have a fairly large yard. This service activity was carried out in Bandar Sari Village, Padang Ratu District, Central Lampung Regency, Lampung Province by providing counseling and demonstrations on vegetable cultivation and aquaponics fish cultivation. From the results of community service activities, it is known that the understanding of community members about fish farming in ponds and hydroponic plants is good. However, these activities are still carried out separately, not combined into one in the form of aquaponics. After conducting counseling and demonstrations, the community's understanding becomes better, so that the community can combine the two cultural activities into one profitable activity.